STUDY OF THE DOLOMITES OF THE JAMANSAI DEPOSIT (Scientific journal of the Fergana State University, 2024)
The chemical and mineralogical composition, physico-chemical properties of dolomite from the Jamansaideposit of the Republic of Karakalpakstan have been studied. According to the results of chemical analysis, the contentof dolomite in the mineral is almost 99%. According to the results of thermographic analysis, the temperature range oftwo stages of dolomite dissociation was determined, it was found that the first stage of dolomite dissociation correspondsto a temperature of 713-766 ° C, and the second-780-820 ° C. It has been shown that the dolomite found in Jamansaican be used as a raw material for the production of magnesia bonds.